Antibacterial activity of selenium nanoparticles/copper oxide (SeNPs/CuO) nanocomposite against some multi-drug resistant clinical pathogens - Ahmed Morad Asaad; Sara A. Saied; Mohammad M. Torayah; N. I. Abu-Elsaad; Samah Mohammed Awad. (BMC Microbiology)
Abstract Background Recent advances in nanomedicine have derived novel prospects for development of various bioactive nanoparticles and nanocomposites with significant antibacterial and antifungal properties. This study aims to investigate some characteristics of the novel Se-NPs/Cu2O nanocomposite such as morphological, physicochemical, and optical properties, as well as to assess the antibacterial activity of this fabricated composite in different concentrations against some MDR Gram-positive and Gram-negative clinical bacterial isolates. Methods The Se-NPs/Cu2O nanocomposite was fabricated using the chemical deposition method. The fabricated nanocomposite was fully characterized by X-Ray diffraction analysis (XRD), fourier transforms infrared spectroscopy (FTIR), and transmission electron microscope (TEM). The antimicrobial activity of Se-NPs/Cu2O was investigated using the standard broth microdilution method. The fabricated Se-NPs/Cu2O nanocomposites were detected as stable and highly crystallized nanospheres with an average size of 98.6 nm. Results The Se-NPs/Cu2O nanocomposite showed a potent antimicrobial activity with MIC values ranged from 6.25 to 12.5 µg/ml for Gram-positive isolates, and 25 to 50 µg/ml for gram-negative isolates. The bactericidal activity was higher for gram-negative isolates with MBC/MIC ratios of 1–2 µg/ml for gram-negative, versus 8 µg/ml for gram positive pathogens. Conclusion These findings would support further research in development of a novel Se-NPs/Cu2O nanocomposite as a promising alternative therapeutic option for improving the quality of patients’ management.